Tagraxofusp, the first CD123-targeted therapy and first targeted treatment for blastic plasmacytoid dendritic cell neoplasm. Issue 10 (3rd October 2019) - Economides, Minas P.; McCue, Deborah; Lane, Andrew A.; Pemmaraju, Naveen
ABSTRACT: Introduction : CD123 or interleukin 3 receptor alpha is overexpressed in multiple hematologic malignancies. Tagraxofusp is an intravenously administered CD123-directed cytotoxin consisting of the fusion of interleukin-3 with a truncated diphtheria toxin payload and was recently approved by the Food and Drug Administration for the treatment of adults and children aged 2 and older with blastic plasmacytoid dendritic cell neoplasm (BPDCN). Areas Covered : In this review, we discuss the use of tagraxofusp in BPDCN, and active clinical trials involving this agent in several hematologic malignancies are also presented. Tagraxofusp has significant efficacy in patients with BPDCN and manageable safety profile, with the most commonly reported adverse events being asymptomatic elevation of alanine and aspartate aminotransferase levels, hypoalbuminemia, peripheral edema, and thrombocytopenia. The most serious side effect is capillary leak syndrome that can be lethal in some cases but the risk may be mitigated by early recognition and intervention. Expert Opinion : Tagraxofusp has been introduced as a novel treatment of BPDCN, a rare hematologic malignancy, for which no standard therapy previously existed. Many patients treated with this agent were able to be bridged to stem cell transplantation, including older patients. In the future, combinations of tagraxofusp with other targeted agents will be explored.